Research on promotion of implementation of clinical practice guidelines(I):the status of implementation and promotion strategies - Xu-Hui LI; Qiao HUANG; Yong-Bo WANG; Si-Yu YAN; Mu-Kun CHEN; Kuang GAO; Yi-Bei SI; Jing GUO; Wen-Bin HU; Ying-Hui JIN (Yixue xinzhi zazhi)
The implementation of clinical practice guidelines is an important form of evidence transformation and a main way to narrow the gap between research results and clinical practice. Af-fected by factors such as low operability, single form of dissemination and application, not timely update, and lack of implementation tools and implementation evaluation tools, the implementation of clinical practice guidelines is still insufficient. Combining the evidence ecosystem framework, constructing guideline implementation evaluation tools, and using knowledge graph and other artificial intelligence technologies to provide theoretical support, effect evaluation tools, and technical paths for the imple-mentation of the guidelines are effective methods to promote the implementation of clinical practice guidelines.